(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This annotation focuses on the phenomenon of word formation through compounding, a productive process that involves combining two or more existing words to create a new word with a distinct meaning. The author investigates the role of compounding in expanding the lexical inventory of a language and analyzes its compositional nature. The annotation explores different types of compounds, such as noun-noun compounds, verb-noun compounds, and adjective-noun compounds, highlighting the structural and semantic relationships between the constituent words. Drawing on linguistic theories and empirical research, the article discusses the cognitive processes involved in compounding and examines the factors that influence the productivity and creativity of compound formation. Furthermore, the annotation addresses the challenges posed by compounding in terms of lexical retrieval and semantic compositionality. Overall, this comprehensive analysis contributes to a deeper understanding of the principles and mechanisms underlying word formation through compounding, shedding light on its significance in lexical expansion and linguistic diversity